3x-(7x-4)=5x-(2x+10)

Simple and best practice solution for 3x-(7x-4)=5x-(2x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(7x-4)=5x-(2x+10) equation:


Simplifying
3x + -1(7x + -4) = 5x + -1(2x + 10)

Reorder the terms:
3x + -1(-4 + 7x) = 5x + -1(2x + 10)
3x + (-4 * -1 + 7x * -1) = 5x + -1(2x + 10)
3x + (4 + -7x) = 5x + -1(2x + 10)

Reorder the terms:
4 + 3x + -7x = 5x + -1(2x + 10)

Combine like terms: 3x + -7x = -4x
4 + -4x = 5x + -1(2x + 10)

Reorder the terms:
4 + -4x = 5x + -1(10 + 2x)
4 + -4x = 5x + (10 * -1 + 2x * -1)
4 + -4x = 5x + (-10 + -2x)

Reorder the terms:
4 + -4x = -10 + 5x + -2x

Combine like terms: 5x + -2x = 3x
4 + -4x = -10 + 3x

Solving
4 + -4x = -10 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
4 + -4x + -3x = -10 + 3x + -3x

Combine like terms: -4x + -3x = -7x
4 + -7x = -10 + 3x + -3x

Combine like terms: 3x + -3x = 0
4 + -7x = -10 + 0
4 + -7x = -10

Add '-4' to each side of the equation.
4 + -4 + -7x = -10 + -4

Combine like terms: 4 + -4 = 0
0 + -7x = -10 + -4
-7x = -10 + -4

Combine like terms: -10 + -4 = -14
-7x = -14

Divide each side by '-7'.
x = 2

Simplifying
x = 2

See similar equations:

| z/17=-19 | | 14-3/4x | | 4-3x=5(x+4) | | 3a+b-45=2a+4b+465.23+-a+507.23b | | 19=4y+7 | | 29+0.15x=20+0.25x | | 2x+3-5x=5x-15+6 | | (2x+1)(2x-1)=4x | | 4y+2=-8/3(8-12y) | | 3a+b-45=2a+4b+465.23+a+507.23b | | 15+.25x=20+0.05 | | 2x+4=9+6x | | -4(x-9)=42 | | 5x-12+7x+4= | | 64m^2+7=16 | | 2x+90=85 | | -3+4=-5-9 | | 2(x+6)=4(3x) | | 4x-8=(x-4) | | 36+N=63 | | 3a+b-45=2a+4b+465.23+a+103b | | 13-x/7=-1 | | -1/5a+7=(-11) | | (x+2x+5)-10=22 | | 5/8x24 | | a/b-45=2a+4b+465.23+a+103b | | 1/4(8x-16)=6x+2 | | ab-45=2a+4b+465.23+a+103b | | -15-(-8)+7= | | ab-45=2a+4b+465.23+a+103ab | | -1-6k=-7k-19 | | 2+25p^2=66 |

Equations solver categories